The Effect of Ginger Drink on the Menstrual Pain Scale (Dysmenorrhea) in Students at Senior High School 2 Bengkulu City in 2022 - Lestari, Maya, Murwati, Murwati; Rustandi, Handi (Student Scientific Journal, 2023)
Dysmenorrhea is a problem of adolescent reproductive health. The incidence of dysmenorrhea in the world is very large, on average almost more than 50% of women experience it. The dysmenorrhea rate in Indonesia is no less high than other countries in the world. The purpose of this study was to see the effect of drinking ginger on the level of menstrual pain (dysmenorrhea) in female students at SMAN 2 Bengkulu City in 2022.Treatment of dysmenorrhea has developed in society, both pharmacologically and non-pharmacologically. The pharmacological approach is by administering analgesic and sedative drugs. While the non-pharmacological approach is by giving ginger drink.The method in this study is quantitative, using a quasy experiment with a pre-post test one group design approach. The sample in the study was 20 respondents who were selected according to the inclusion and exclusion criteria. This study uses the Wilcoxon statistical test.This study used a ginger drink concoction that can be used to reduce menstrual pain dysmenorrhea in female students at SMAN 02 Bengkulu City with a dose of 200 ml/day of ginger water given in the morning during the first menstrual day to the third day of menstruation.The results showed that the mean value of dysmenorrhea before intervention was .5.45 with a standard deviation value of 0.686. the mean value of dysmenorrhea after the intervention was 3.10 with a standard deviation value of 0.641. The results of the Wilcoxon test obtained a p value of 0.000 <0.05, meaning that the effect of ginger drink on the level of menstrual pain (dysmenorrhea) in students at SMAN 2 Bengkulu City in 2022.The conclusion in this study is ginger drink can overcome menstrual pain. It is hoped that adolescents who experience dysmenorrhea will use ginger drinks.